NILAI MORAL DALAM PERSPEKTIF SOSIOLOGI SASTRA PADA NOVEL PARADIGMA KARYA SYAHID MUHAMMAD - Rachman, Anita Kurnia; Susandi, Susandi (University of Brawijaya, 2021)
Moral values contained in society are also contained in the novel. The problem of moral values appears in the novel because moral values are the foundation of people's attitudes and behavior in daily life that are also experienced by the characters in the novel. This study aims to analyze the moral value of human relations with oneself, human relations with other humans, human relations with the natural environment, and human relations with God in the Novel Paradigm by Syahid Muhammad. This research is a qualitative research with a sociological approach to literature. Data in the form of narrative quotations, phrases, clauses, and sentences. The main instrument, namely the research itself. Data analysis is done by organizing data, describing it in units, arranging into patterns, and making conclusions. The results of the study, namely 1) The moral values of human relations with yourself include self-introspection, wise attitudes, intelligent thinking, and working hard. 2) The moral values of human relations with other humans include compassion, intimacy, counseling, filial piety to parents, praise others. 3) The moral value of human relations with the environment which includes admiring and respecting the universe as the creation of God Almighty. 4) The moral value of human relations with God which includes gratitude and prayer.